Pengembangan Kompetensi Digital Tenaga Pendidik di Era Artificial Intelligence: Tantangan dan Strategi pada Sekolah di Bawah Yayasan Al Kautsar - Rina Eka Widjayanti; Adityas Wahyungsih; Meika Kurnia Puji Rahayu Dyah Anggraeni (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
This study aims to analyze the challenges and formulate strategies for developing the digital competencies of educators in adopting Artificial Intelligence (AI) at Yayasan Al Kautsar. The research employed a qualitative approach using a descriptive case study method. Data were collected through in-depth interviews, participatory observation, and document analysis involving 22 educators from early childhood education to junior high school levels. The findings indicate that intensive mentoring contributed to improving educators’ understanding and skills in using AI as a tool for administrative tasks and the development of instructional media. The main challenges identified include initial anxiety toward AI, limited digital literacy, unstable internet connectivity, disparities in device specifications, and the absence of standardized internal training. This study recommends a human resource development model based on peer learning, continuous training, and the strengthening of schools’ digital infrastructure. The findings emphasize that the successful integration of AI in education is determined not only by the individual readiness of educators but also by organizational support and the broader technological ecosystem.